2H‐MoS2 as an Artificial Solid Electrolyte Interface in All‐Solid‐State Lithium–Sulfur Batteries. Issue 20 (23rd August 2020) - Kızılaslan, Abdulkadir; Çetinkaya, Tuğrul; Akbulut, Hatem
Abstract: All‐solid‐state lithium‐ion batteries are considered the next‐generation energy storage systems. However, certain problems arise from the degradation of anode–electrolyte interface hindering their use especially when lithium is used as an anode. Herein, lithium metal anode surface is modified by an artificial 2H‐MoS2 layer to prevent the contact between highly reactive lithium and solid electrolyte without sacrificing the lithium ion transport. The stabilization of the electrode/electrolyte interface is attributed to the electrochemical stability of the 2H‐MoS2 layer. Besides, high ionic conductivity and selective sieving nature of layered MoS2 neither prevents the electrochemical reactions nor increases the total impedance of the cell. Electrochemical stability of the electrode/electrolyte interface is shown by long‐term chronoamperometry and chronovoltammetry tests. By stabilizing electrode/electrolyte interface, initial and final discharge capacities of 675.8 and 584.1 mAh g −1, respectively, is obtained at 0.4 mA cm −2 current density in MoS2 @Li/Li7 P3 S11 /S. After 200 cycles, discharge capacity fade is obtained as 13.58% and 27.3% for the cells assembled with MoS2 @Li and bare Li anodes, respectively. Abstract : The surface of the lithium metal is coated with 2H‐MoS2 and utilized as a solid‐electrolyte interface to alleviate the degradation of solid‐electrolyte in contact with lithium anode. Electrochemical stability of the interface is verified by long‐term chronoamperometry and chronovoltammetry analyses techniques. The effect of the coating is shown in the cells assembled with and without MoS2 ‐coated lithium anode in all‐solid‐state batteries.